ANALISIS POTENSI PEMBENTUKAN WOMEN PRENEUR COMMUNITY (WPC) DALAM RANGKA PENGEMBANGAN PRODUK EKONOMI KREATIF DAN INOVATIF BERBASIS DIGITAL: STUDI PADA MAHASISWI UNIVERSITAS SAMAWA - Asmini, Asmini; Ismawati, Ismawati; Yuliana, Yuliana; Umar, Ardin (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study analyzes the potential formation of a Women Preneur Community (WPC) to develop creative and innovative digital-based economic products among female students at Samawa University, Sumbawa, using a Human Resource Management (HRM) approach. The focus identifies competencies, intrinsic motivation, and manageable internal supporting-inhibiting factors to strategically drive creative economy product development. A descriptive qualitative approach was employed. Primary data were gathered through in-depth interviews with 10 entrepreneurship-interested female students, Focus Group Discussions (FGD) involving 2 entrepreneurship lecturer representatives, and observations of business talents. Data analysis applied the interactive model of Miles and Huberman. Findings reveal that Samawa University female students possess substantial potential as innovative creative women preneurs, supported by high digital adaptability and strong intrinsic motivation. University backing aligns with the Tri Dharma of Higher Education. WPC formation, structured around HRM functions—planning, talent training and development, performance management, and rewards—offers an effective strategy to address potential management gaps and establish a structured, sustainable development platform. The study's novelty lies in applying an HRM perspective to empower campus women preneurs, rarely explored in depth, enabling actualization of tangible digital-visioned creative economy products.